2009
DOI: 10.2527/jas.2009-1860
|View full text |Cite
|
Sign up to set email alerts
|

Does cardiovascular performance of modern fattening pigs obey allometric scaling laws?

Abstract: In view of the remarkable decrease of the relative heart weight and the relative blood volume in growing pigs, we investigated whether cardiac output (CO) and stroke volume (SV) of modern growing pigs are proportional to body mass (M), as predicted by allometric scaling laws: CO (or SV) = a.M(b), in which b is a multitude of 0.25 (quarter power scaling law). Specifically, we tested the hypothesis that CO scales with M to the power of 0.75 (CO = a.M(0.75)) and SV scales with M to the power of 1.00 (SV = a.M(1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…In conclusion, we previously reported that the proposed disproportionate development of the cardiovascular system in modern fattening pigs is not apparent in growing pigs with BW up to 75 kg, even when the cardiovascular system is stressed during submaximal exercise (van Essen et al, 2009). The present study in young growing and adult pigs demonstrates for the first time that adult sows exhibit CO and SV that are disproportionately low for their BW.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In conclusion, we previously reported that the proposed disproportionate development of the cardiovascular system in modern fattening pigs is not apparent in growing pigs with BW up to 75 kg, even when the cardiovascular system is stressed during submaximal exercise (van Essen et al, 2009). The present study in young growing and adult pigs demonstrates for the first time that adult sows exhibit CO and SV that are disproportionately low for their BW.…”
Section: Discussionmentioning
confidence: 78%
“…However, information regarding the cardiovascular system of the pig in relation to BW is fragmentary, and CO measurements, especially in growing pigs, are lacking to date. Recently, we (van Essen et al, 2009) addressed this question by collecting and analyzing CO and SV data of 60 growing pigs, with BW ranging from 22 to 75 kg, both at rest and during strenuous treadmill exercise. The results of that study showed for the first time that both CO and SV obeyed allometric scaling laws in pigs up to 75 kg, not only under resting conditions, but also during treadmill exercise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that although pigs and humans have similar cardiac physiology with comparable heart rate and cardiac output [ 24 , 25 ], minor differences between the human and porcine LV ECMs have been reported [ 20 ]. Specifically, collagens II, V, and VI were identified only in the porcine and not the human LV ECM, but the relative abundance of ECM proteins between the species was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that swine of the body weights used in this study obey allometric scaling laws with regard to a linear relationship between cardiac output and body weight (van Essen et al . ). Arteriolar constrictor responses are presented as percentage possible constriction calculated as [( D b – D d )/ D b ] × 100, where D b is baseline diameter and D d is diameter after a drug intervention.…”
Section: Methodsmentioning
confidence: 97%